PENGARUH DUKUNGAN SOSIAL TEMAN SEBAYA TERHADAP PERILAKU SEKSUAL PRANIKAH REMAJA DI KECAMATAN MUARA WAHAU KUTAI TIMUR - Nur Kumalasari Suratno; Mulya Virgonita I.W; MM Shinta Pratiwi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine the influence of peer social support on premarital sexual behavior among adolescents in Muara Wahau District, East Kutai. The background of this research lies in the developmental dynamics of adolescence, which is highly vulnerable to social environmental influences, particularly from peer groups, in shaping attitudes and sexual behaviors. A quantitative approach with a correlational method was employed, involving 100 adolescent respondents aged 15–19 years selected through purposive sampling. Data were collected using the Peer Support Questionnaire (PSQ) to measure peer social support and the Youth Sexual Behavior Inventory (YSBI) to assess premarital sexual behavior. The results of simple linear regression analysis indicate a positive and significant effect of peer social support on premarital sexual behavior (p < 0.05), with an R² value of 0.232. This finding suggests that higher levels of peer social support are associated with greater tendencies of adolescents to engage in premarital sexual activities. The study highlights that peer support can serve a dual role: either as a protective factor or as a risk factor, depending on the values embedded within the peer relationship. Therefore, it is crucial to develop healthy peer mentoring systems grounded in educational and value-based approaches to prevent risky sexual behaviors among adolescents.